INDUSTRIAL CLUSTER - AS A STRATEGIC DIRECTION OF INCREASING INDUSTRIAL COMPETENCE (Marketing Journal, 2025)
This article analyzes strategic directions for enhancing industrial potential through the formation and development of industrial clusters. The author thoroughly examines the principles of clustering, the structural elements of the cluster model, and their advantages for various industri al sectors. Key functional aspects of clusters — such as production, logistics, innovation, research activities, and infrastructural integration — are highlighted. Based on both international and national experiences, the article substantiates the contribution of industrial clusters to economic growth and increased competitiveness, as well as the synergistic effect generated by higher levels of inter - enterprise coope ration and specialization. Recommendations are proposed for developing clusters in Uzbekistan, focusing on necessary infrastructure, institutional frameworks, and investment approaches.
Keywords: industrial cluster; industrial potential; cooperation; economic development; strategic development; competitiveness